2011
DOI: 10.1007/s11430-011-4257-3
|View full text |Cite
|
Sign up to set email alerts
|

Rates of temperature change in China during the past 2000 years

Abstract: Using 24 proxy temperature series, the rates of temperature change in China are analyzed at the 30-to 100-year scales for the past 2000 years and at the 10-year scale for the past 500 years. The results show that, at the 100-year scale, the warming rate for the whole of China in the 20th century was only 0.6±1.6°C/100 a (interval at the 95% confidence level, which is used hereafter), while the peak warming rate for the period from the Little Ice Age (LIA) to the 20th century reached 1.1±1.2°C/100 a, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Chinese historical documents [41,[50][51][52] showed that temperatures in eastern China at that time were the coldest in the past 2000 years. However, the SST decreased gently, with only low amplitude.…”
Section: Modulation Effect Of the Yellow Sea Warm Current To The Sstmentioning
confidence: 99%
“…Chinese historical documents [41,[50][51][52] showed that temperatures in eastern China at that time were the coldest in the past 2000 years. However, the SST decreased gently, with only low amplitude.…”
Section: Modulation Effect Of the Yellow Sea Warm Current To The Sstmentioning
confidence: 99%
“…In China, the problem of climate change over the past two millennia has been of longstanding interest to the paleoclimatic community (e.g., Gong and Hameed, 1991;Shi et al, 1999;Zheng et al, 2001;Yang et al, 2002;Ge et al, 2003;Ge et al, 2004;Holmes et al, 2009;Ge et al, 2011;Tan et al, 2011;Hao et al, 2012;Ge et al, 2013a;Ge et al, 2013b;Yan et al, 2015a;Yan et al, 2015c;Yan et al, 2015d;Hao et al, 2016;Yang et al, 2016). However, almost all of these studies were based on terrestrial proxy records, historical documentary data, and simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…In China, a large number of historical climate reconstructions with information from historical documents have been completed (Ge et al , 2008, 2010; Ge and Zheng, 2010). For instance, Chu (1973) reconstructed temperature changes for the past 5000 years; Zhang (1980) and Wang et al (1998) reconstructed temperatures with a 10‐year resolution for the past 500 years for the mid‐lower region of the Yangtze river and eastern China, respectively; Ge et al (2003) reconstructed temperatures for the past 2000 years with 10–30‐year resolution for eastern China.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the Eastern Asia summer monsoon (EASM) area of China underwent a transition from the Little Ice Age to a modern warming climate during the latter half of the 19th century (Ge et al , 2003). In this transition period, the temperature was estimated to increase at a rate of about 0.5 °C per 30 years (Ge et al , 2011b). With such a background of climate warming, the precipitation in northern China associated with the EASM had an increasing trend, and moreover, decadal and annual variations were also found (Zheng et al , 2006); the rainy season in the northwest edge of the EASM area of China was lengthened, and this phenomenon was attributed to the stronger East Asia Monsoon (Ge et al , 2011a).…”
Section: Introductionmentioning
confidence: 99%